Defluorosilylation of fluoroarenes and fluoroalkanes. Issue 1 (December 2018) - Cui, Benqiang; Jia, Shichong; Tokunaga, Etsuko; Shibata, Norio
Abstract Direct activation of carbon–fluorine bonds (C–F) to introduce the silyl or boryl groups and generate valuable carbon–silicon (C–Si) or carbon–boron (C–B) bonds is important in the development of synthetically useful reactions, owing to the unique opportunities for further derivatization to achieve more complex molecules. Despite considerable progress of C–F bond activation to construct carbon–carbon (C–C) and carbon–heteroatom (C–X) bond formation, the defluorosilylation via C–F cleavage has been rarely demonstrated. Here, we report anipso -silylation of aryl fluorides via cleavage of unactivated C–F bonds by a Ni catalyst under mild conditions and without the addition of any external ligand. Alkyl fluorides are also directly converted into the corresponding alkyl silanes under similar conditions, even in the absence of the Ni catalyst. Applications of this protocol in late-stage defluorosilylation of potentially bioactive pharmaceuticals and in further derivatizations are also carried out. Transformation of strong C-F bonds into C-Si bonds is an extremely useful strategy for further derivatization of organic molecules. Here, the authors report a nickel-catalyzed strategy to convert aryl fluorides into sylylated arenes while defluorosilylation of alkyl fluorides is achieved under metal-free conditions.